The Impact of Liquidity, Solvability, Activity, Profitability, Asset Growth, and Sales Growth to Systematic Risk With Firm Size as Moderating Variable on Consumer Non-Cyclicals Company Listed in Indonesia Stock Exchange 2017-2021 - Siti Lestari; Lis Sintha (PT Mattawang Mediatama Solution, 2022)
Investors need useful information as a signal to decide on investment because investment activity contains risk of uncertainty that will occur in the future that can not be handled by diversification which is called systematic risk. Systematic risk is calculated by beta stock which the companies have different beta values. Therefore, this research aims to analyze the impact of financial information on the beta stock in sector consumer non-cyclicals listed on Bursa Efek Indonesia (BEI) with the observation period 2017-2021. Respon variables in this research are liquidity, solvability, activity, profitability, asset growth, and sales growth, with firm size as the moderating variable. Population in this research was 103 companies, then got 40 companies after doing the purposive sampling method, so there were 200 units of analysis with five years of analysis. Data analysis method using SEM-PLS analysis with software SmartPLS. The results show that liquidity has a significant negative impact on systematic risk. Solvability, profitability, and sales growth significantly positively affect systematic risk. Activity and asset growth are not relevant to systematic risk. The moderation test result proves that firm size significantly adequates the impact of liquidity, profitability, and sales growth on systematic risk. Firm size does not significantly adequate the impact of solvability, activity, and asset growth on systematic risk.